Molecular Genotyping Of Growth Hormone And Growth Hormone Receptor In Surti Buffalo - Janmeda, Mamta; Vataliya, P.H. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The study was conducted to find out polymorphism of different growth hormone (bGH) and growth hormone receptor loci (bGHR) by using PCR-RFLP technique and association of different polymorphic bGH and bGHR loci with milk production in Surti buffalo. 72 blood samples of Surti buffalo were collected from LRS, Navsari Agricultural University, Gujarat. The DNA samples were subjected to PCR amplification using bGH and bGHR specific primers GH1, GH2, GH3 and GHR1. The PCR products of GH1 (427 bp), GH2 (891 bp), GH3 (441bp) and GHR1 (approx 640 bp) loci were digested with Alu 1, Msp 1, Hae III and Mae II restriction enzymes respectively. Only AA, CC, FF and RR genotypes were found in Surti buffalo. All the bGH and bGHR loci studied were monomorphic indicating monomorphism at these loci may be a species characteristic of Surti buffalo.